Dialect Leveling and Koine Formation Among Urban Igbo Speakers: A Socio-Phonetic Investigation - Ndibe, Princess Ngozi; Chika, Anaekwe Rita (Education and Development Research, 2026)
This paper examines dialect leveling and koine formation among urban Igbo speakers from a socio-phonetic perspective. Drawing on theories of dialect contact and koineisation, as well as descriptive studies of Igbo dialectal diversity, the research investigates patterns of convergence, retention, and innovation in urban Igbo speech. A mixed-methods socio-phonetic design was employed, combining sociolinguistic interviews, reading tasks, and perception tests with acoustic analysis and quantitative variationist methods. The study was conducted in Onitsha, Enugu, and Awka and involved 120 stratified participants, focusing on variation in vowel quality, consonant realization, and tonal patterns. Findings reveal systematic phonetic changes, including vowel centralisation, consonant reduction, and tonal simplification, which collectively contribute to the emergence of an urban Igbo koine. These changes are strongly associated with social factors such as age, mobility, prestige orientation, media exposure, education, and social networks. The results suggest that rapid internal migration, intermarriage, and sustained contact in major commercial and administrative centers have accelerated dialect leveling, resulting in reduced variation and increased convergence across speakers. The emerging koine is perceptually linked to prominent urban hubs, particularly Onitsha and Enugu. The paper discusses the methodological framework, empirical findings, and social conditioning of phonetic change, and concludes by outlining implications for Igbo language policy, standardization, and future socio-phonetic research.